Estudo da eletro-osmose em solos finos - Castello Branco, José Eduardo Saboia (1978)
By using laboratory experiments, electro-osmosis in fine grained soils was surveryed under two dffferent aspects: the electro-drainage and the electro-hardenig. In relation to the electro-hardening, solutions of chemical products were injected into soil specimens by electro-osmosis, and the effects on the limits of Atterberg observed. With respect to electro-drainage, specimens of an organic clay were consolidated under electric gradients, and their behavior observed during primary and secondary compression. For this experimental study, two different apparatus were designed to accomplish the objectives above mentioned. A detailed description of the equipment is given. Past field and laboratory experiments have been reviewed, and the main features were summarized to serve as a guide for future applications.